Key account relationship management: the moderating effects of relationship duration and transaction volume. Issue 7 (11th June 2018) - Yeh, Jian He; Wang, Stephen W.; Hsu, Maxwell K.; Swanson, Scott
ABSTRACT: This study investigates the impact of three relational benefits (i.e. financial benefits, human interaction benefits, preferential treatment benefits) on switching barriers, customer satisfaction, and behavioral loyalty for key accounts in the context of the air express delivery industry in Taiwan. Empirical results indicate that relational benefits impact switching barriers, switching barriers influence customer satisfaction and loyalty, and customer satisfaction effects loyalty. Findings also confirm most of the hypothesized moderating effects for relationship duration and transactional volume on the relationship between relational benefits and switching barriers. Specifically, long-term key accounts place greater emphasis on the human interaction and preferential treatment benefits. Key accounts that have less established relationships based on the length of business relationship place more importance on financial benefits. Financial benefits were found to have a positive influence on switching barriers only for low annual transactional volume clients, while both human interaction benefits and preferential treatment benefits have positive effects for both low and high transactional volume key accounts.